Emergency Department Visits Within 90 Days of Total Ankle Arthroplasty - Philip P. Ratnasamy BS; Alexander J. Kammien; Michael J. Gouzoulis BS; Jonathan N. Grauer MD (Foot & Ankle Orthopaedics, 2022)
Category: Arthroscopy; Ankle Introduction/Purpose: Emergency department (ED) visits following total ankle arthroplasty (TAA) may impact patient satisfaction and healthcare cost. Elucidating the timing of and risk factors for ED visits in this patient population might help facilitate targeted risk reduction strategies. Methods: This retrospective cohort study utilized data from the 2010 to 2019 M91Ortho PearlDiver administrative dataset to identify patients who underwent TAA with at least 90 days of follow-up. Patient factors were extracted including: age, sex, Elixhauser Comorbidity Index (ECI), region of the country in which their procedure was performed (midwest, northeast, south, west), and insurance plan (commercial, Medicaid, Medicare). The incidence, timing, frequency, and primary diagnoses for 90-day postoperative ED visits were identified and interpreted in the context of one-year postoperative ED visit baseline data. Univariate and multivariate logistic regression analyses were used to determine risk factors for such ED visits. Results: Of 7,600 TAA patients identified, 743 (9.8%) visited the ED within 90 days of their procedure. Of those who visited the ED, one ED visit was reported for 571 patients, two for 117 patients, three for 26 patients, and four or more visits for 29 patients. 37.2% of all ED visits occurred within two weeks following surgery; weekly visits returned to within 0.5% of the population baseline by three weeks after surgery. 90-day readmissions were identified for 289 patients (3.80%) of the cohort. Multivariate analysis revealed several predictors of ED utilization following TAA: younger age (odds ratio (OR) 1.40 per decade decrease), female sex (OR 1.18), higher ECI (OR 1.36 per 2-point increase), and Medicaid coverage (OR 2.74; 1.92-3.90 relative to Medicare) (p < 0.05 each). Regarding reasons for ED visits, surgical site issues were identified for 74.4%, with the most common reason being surgical site pain (60.4%). Conclusion: Of 7,600 TAA patients, 9.8% returned to the ED within 90 days of surgery, with predisposing demographic actors identified. The highest incidence for these ED visits was in the first two postoperative weeks, with surgical site pain being the most common reason. By identifying the timing, predisposing factors, and reasons for ED visits following TAA, targeted care pathways should be able to be adjusted to minimize their occurrence, improve patient experience, and minimize health care utilization/costs.